A survey of tap water quality in Kuala Lumpur - Ong, C.; Ibrahim, S.; Gupta, B.S. (Taylor & Francis, 2007)
A safe drinking water programme known as The National Drinking Water Quality Surveillance Programme (NDWQSP) was launched by the Ministry of Health, Government of Malaysia in 1983 to ensure safe practices in water treatment and distribution. The aim of this work was to assess the effectiveness of this programme in the improvement of tap water quality in and around Kuala Lumpur. The results indicate that there was no microbial contamination in 100 random samples collected from 20 selected areas. Other quality parameters such as colour, pH, turbidity, hardness, magnesium, sulphate and chloride were within acceptable limits. Heavy metals such as Cu2+, Pb2+, Cr (total), Ni2+, Cd2+, Fe (total) and Mn (total) were also under control. The only exception was Ba2+, which did not comply with the standard and was up to ten times higher than the guideline value. Moreover, there was significant variation in water quality as indicated by the test results.